Big Five Personality Profiles in the Norwegian Special Operations Forces - Skoglund, Tom Hilding; Brekke, Thor-Håvard; Steder, Frank Brundtland; Boe, Ole (Frontiers in Psychology, 2020)
This study is the first to report on Big Five personality traits of employees in the Norwegian military Special Operations Forces (NORSOF). Three research questions were formulated for this study, aiming to investigate (1) whether age, number of combat-deployments and rank (OR/OF) had an impact on the personalities of NORSOF employees, (2) possible personality differences between personnel organized in the underlying departments of the NORSOF, and (3) if there were personality differences between SOF-operators and conventional forces applicants. SOF-operators from the Norwegian Special Operations Commando (FSK) and the Norwegian Naval Special Operations Commando (MJK) constituted 40% of the total NORSOF sample (N = 190), whilst the term SOF-support categorized the larger proportion of non-operators. Results indicated that younger employees tended to be lower on emotional stability than older colleagues, and that those without any combat-deployments were somewhat higher on agreeableness and a bit lower on emotional stability relative to employees with such experience. Additionally, personnel with officer ranks (OF) were higher on extraversion compared to specialists (OR). Results did not show any significant intradepartmental differences in mean personality trait scores. Compared to male applicants for basic officer training in conventional forces (N = 662), SOF-operators (all males) were less extroverted, less agreeable and slightly more emotionally stable. The authors conclude that the NORSOF attracts and recruits personnel with similarities in their Big Five personalities. Furthermore, we suggest that the personality profile that emerged for the “average” Norwegian SOF-operator is a functional one, especially when considering the desired future image of the Special Forces operative as a Warrior-Diplomat.